Credit Risk Management in Banks of a Developing Economy: The Case of Cameroon - Chi, Marcus (2007)
Credit is the largest element of risk in the books of most banks and failure in the management of credit risk weakens individual banks and in some cases the banking system as a whole, thereby contributing to many episodes of financial instability and distress (see Jackson & Perraudin, 1999).